Clinical Efficacy “Armadin” in Patients with the Condition of Alcohol Withdrawal - Ponomaryov, V.; Slyusar, V.; Voloshinа, D.; Lebedynets, D.; Vovk, V. (Psychiatry, Neurology and Medical Psychology, 1970)
In this article we describe current data about the problem of alcoholism and alcohol dependence syndrome,the pathogenesis of alcohol dependence and withdrawal. We have shown the efficacy of the drug with a strong antioxidant andantihypoxic effect – «Armadin» - in state of alcohol withdrawal.High efficiency, rapid onset of therapeutic action, tranquilizing effect of the drug, no side effects and safety of the drug led to the recommendation for the treatment of patients with alcoholism.